An Analysis on Various Improvements In Establishing Lesson Plan For English Teachers at School Level: Enhancing Lesson Plan Development for English Teachers (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Lesson Planning" serves as a guide for noviceteachers who need to create formalized lesson plans. The paper covers why,when, and how teachers plan lessons, as well as basic lesson plan principlesand a lesson plan improvement. A sample lesson plan is provided in the contextof a weekly overview, module overview, and course overview.